(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Ultrasound-guided erector spinae plane block (ESPB) is an innovative technique in which local anesthetic is placed between the deep fascial plane of the erector spinae muscle and superficial to the tip of the transverse process. ESPB is a safe, innovative strategy that is easy to perform and ensures good postoperative analgesia in radical mastectomy Aim: to o compare between the analgesic effect of two different volumes and concentrations of local anesthetics [20ml lidocaine 2% (400mg) versus40ml lidocaine 1% (400mg)]. Subjects and Methods: Our study is a comparative study that compare between two volumes of local anesthetic with fixed drug mass used in the ultrasound guided erector spinae plane block in patients undergoing modified radical mastectomy 82 patients were allocated in two equal groups, group L received 20 ml of lidocain 2% and group H received 40 ml of lidocain 1%. First 24 hours postoperative morphine consumption, VAS score, duration of the surgery, incidence of complications, postoperative nausea and vomiting and also haemodynamics were recorded and statistically analyzed. Results: There was no statistical significant between the two groups regarding morphine consumption or VAS score. Postoperative nausea and vomiting were insignificantly different between the two groups. Conclusion: increasing the volume of the local anesthetic with fixed drug mass will not effect the efficacy of the block in decreasing postoperative VAS score and morphine consumption in patients undergoing modified radical mastectomy.